Language awareness and its importance in French Language Learning among the students at the Public Higher Educational Institutions in Malaysia - Hussin, Omrah Hassan @; Mohamad, Ab Halim; Roslan, Amirah Syazwani (Human Resource Management Academic Research Society, 2023)
The development of French Language Learning and Teaching has been spreading in the Malaysian education system since the 1980s. Subsequently, French Foreign Language (FFL) teaching and learning are currently spreading in Malaysia, notably at the Public Higher Educational Institutions (IPTA), in compliance with the Malaysian government’s globalization goals. The current study seeks to determine the students’ awareness and the significance of French Language Learning (FLL) at the respective Public Higher Educational Institutions (IPTA) in Malaysia. The present analytical study involves 329 students from twelve IPTAs: UITM, UKM, UPM, UPNM, UMK, USM, UM, USIM, UTM, UPSI, UUM, and UMT. The current qualitative examination of FFL students' replies to their resolve to learn a certain foreign language demonstrates that language awareness and importance are intertwined in theirs language learning success.